Adaptasi Budaya Masyarakat Pada Masa Pandemi Covid-19 - Agus Sukirno; Abdul Hafizd Sufyana; Alwansyah Rifa’i; Annisaa Rahmah; Arini Sisi Nabillah; Ari Alfianyah (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2021)
This study focuses on the Duri Kosambi community, especially the RT.06 RW.05 environment which has adapted in the economic, education, religious, environmental, health, reality therapy sectors to social impacts during the Covid-19 pandemic. In handling this case, the community and RT staff work together to improve and maintain environmental health. In addition to improving and maintaining environmental health in this area, there is also a Ceria Reading Park which contributes to improving children's education. This study on the adaptation of community culture during the Covid-19 period also shows how to improve the welfare of the community and must adapt during the Covid-19 Pandemic. Keywords: Economy, Education, Religion, Environment, Health, Reality Therapy, Covid-19 Pandemic.